Coordination and binding geometry of methyl-coenzyme M in the red1m state of methyl-coenzyme M reductase. - Hinderberger, D; Ebner, S; Mayr, S; Jaun, B; Reiher, M; Goenrich, M; Thauer, R; Harmer, J (2008)
Methane formation in methanogenic Archaea is catalyzed by methyl-coenzyme M reductase (MCR) and takes place via the reduction of methyl-coenzyme M (CH3-S-CoM) with coenzyme B (HS-CoB) to methane and the heterodisulfide CoM-S-S-CoB. MCR harbors the nickel porphyrinoid coenzyme F430 as a prosthetic group, which has to be in the Ni(I) oxidation state for the enzyme to be active. To date no intermediates in the catalytic cycle of MCRred1 (red for reduced Ni) have been identified. Here, we report a detailed characterization of MCRred1m ("m" for methyl-coenzyme M), which is the complex of MCRred1a ("a" for absence of substrate) with CH3-S-CoM. Using continuous-wave and pulse electron paramagnetic resonance spectroscopy in combination with selective isotope labeling (13C and 2H) of CH3-S-CoM, it is shown that CH3-S-CoM binds in the active site of MCR such that its thioether sulfur is weakly coordinated to the Ni(I) of F430. The complex is stable until the addition of the second substrate, HS-CoB. Results from EPR spectroscopy, along with quantum mechanical calculations, are used to characterize the electronic and geometric structure of this complex, which can be regarded as the first intermediate in the catalytic mechanism.